Pengaruh Pemberian Konseling Gizi terhadap Penurunan Kadar Kolesterol Darah - Al Rahmad, Agus Hendra (Jurnal Kesehatan, 2018)
Technological and socioeconomic advances resulted in dietary changes from the traditional diet to the western diet such as high-calorie fast food and fat, thus impacting the high prevalence of cholesterol in the community. One effort to reduce blood cholesterol can be done through consultation or counseling with a nutritionist. The study aimed to measure the effect of nutritional counseling on the decrease of cholesterol. This quasi-experimental study has used a sample of 48 patients of health center in the Banda Aceh City, divided into case and control groups through non-random assignment. Cholesterol data obtained through laboratory blood tests, and the tool used for its testing is Autocheck  with scale ratio, while the variable method of counseling is done face to face with a tool leaflet. Analysis using a t-test. The results showed a decrease in blood cholesterol in patients given nutritional counseling using a leaflet medium of 20,2 mg/dl (p=0,000), while in the control group (counseling without media) also showed a decrease in cholesterol levels of 6,9 mg/dl (p=0.001). Counseling methods using leaflets have a better value of effectiveness than without the media. Conclusion, the provision of nutrition counseling is very influential on the decline in blood cholesterol, and the use of media leaflets better in nutrition counseling. Suggestion, every health services should cooperate with universities to conduct nutritional counseling routinely and become one of program priority in the handling of degenerative diseases.